Reactive oxygen and oxidative stress tolerance in plant pathogenic Pseudomonas. - Fones, H; Preston, G (2012)
Reactive oxygen species (ROS) are a key feature of plant (and animal) defences against invading pathogens. As a result, plant pathogens must be able to either prevent their production or tolerate high concentrations of these highly reactive chemicals. In this review, we focus on plant pathogenic bacteria of the genus Pseudomonas and the ways in which they overcome the challenges posed by ROS. We also explore the ways in which pseudomonads may exploit plant ROS generation for their own purposes and even produce ROS directly as part of their infection mechanisms.